Understanding the determinants and consequences of HIV status disclosure in Manicaland, Zimbabwe: cross-sectional and prospective analyses. Issue 12 (2nd December 2021) - Goodwin, Theodora; Gregson, Simon; Maswera, Rufurwokuda; Moorhouse, Louisa; Nyamukapa, Constance
ABSTRACT: Few longitudinal studies have measured trends and effects of disclosure over ART scale-up in general-population samples. We investigated levels, determinants and outcomes of disclosure to relatives and partners in a large general-population cohort in Zimbabwe. Trends in disclosure levels from 2003 to 2013 were analysed, and multivariable logistic regression was used to identify determinants. Longitudinal analyses were conducted testing associations between disclosure and prevention/treatment-related outcomes. Disclosure to anyone increased from 79% to 100% in men and from 63% to 98% in women from 2003 to 2008; but declined to 89% in both sexes in 2012–2013. More women than men disclosed to relatives (67.8% versus 44.4%; p  < 0.001) but fewer women disclosed to partners (85.3% versus 95.0%; p  < 0.001). In 2012–2013, secondary/higher education, being single, and experience of stigma were associated with disclosure to relatives in both sexes. Partner characteristics and HIV-group attendance were associated with disclosure to partners for women. Reactions to disclosure were generally supportive but less so for females than males disclosing to partners (92.0% versus 97.4%). Partner disclosure was weakly associated ( p  < 0.08) with having had a CD4 count or taken ART at follow-up in females. To conclude, this study shows disclosure is vital to HIV prevention and treatment, and programmes to facilitate disclosure should be re-invigorated.